Hematological Adaptations to Altitude Training in Female Water Polo Players: A Case Report of a World Championships Medal-Winning Team - Iñigo Mujika; Jocelyn Mara; Irina Zelenkova; Rodrigo Zacca; David B. Pyne (Sports)
Background: The effective monitoring of athletes’ adaptation is crucial to optimize the outcomes of altitude camps and minimize the risk of maladaptation to the hypoxic stress and intensive training. This case report assessed the hematological adaptations in 22 world-class female water polo players during a 16-day ‘live high-train high’ (LHTH) altitude camp (2320 m) and evaluated the differences between selected (n = 13) and non-selected (n = 9) players and between playing positions. Methods: Hematological parameters, including total hemoglobin mass (tHBmass) and blood volume, were measured before and after the camp. Resting heart rate, peripheral oxygen saturation, body mass, fatigue, and sleep were monitored daily. Results: Relative tHbmass increased PRE to POST (5.4 ± 5.1%, range −3.9–20.2), but blood volume did not change (p = 0.797). Erythrocyte count, hemoglobin concentration, hematocrit, and red cell distribution width increased PRE–POST (p < 0.001, ES = 1.21–2.69), while mean corpuscular volume and hemoglobin decreased (p < 0.001, ES = 0.51 and 0.72, respectively). No substantial differences were observed in the hematological parameters between selected and non-selected players. There was a large difference in the change in relative blood volume between centers (n = 4, PRE 74.1 ± 5.4, POST 69.7 ± 5.9 mL/kg; mean ± SD) and field players (n = 15, PRE 80.8 ± 10.6, POST 82.8 ± 6.8 mL/kg; adj p = 0.046, ES = 1.15) and between centers and goalkeepers (n = 3, PRE 89.7 ± 9.6, POST 82.0 ± 7.1 mL/kg; adj p = 0.046, ES = 1.62). Conclusions: A 16-day LHTH camp can induce favorable hematological adaptations in world-class women’s water polo players, without substantial differences between selected and non-selected players, and larger increases in field players.